Sagot :
[tex]\huge\bold\color{blue}{Answer:}[/tex]
What value of x that will satisfy the equation:
(x − 2)(3x) + (2x − 1)(x + 4) = (5x − 1)(x + 1)?
- [tex]\large\tt\red{x \: = \: - \: 1}[/tex]
[tex]\huge\bold\color{blue}{Solution:}[/tex]
(x − 2)(3x) + (2x − 1)(x + 4) = (5x − 1)(x + 1)
= (3x² - 6)x +(2x - 1)(x + 4) = (5x - 1)(x + 1)
= 3x² - 6x +(2x - 1)(x + 4) = (5x - 1)(x + 1)
= 3x² - 6x +2x² + 7x - 4 = (5x - 1)(x + 1)
= 5x² + 6x + 7x - 4 = (5x - 1)(x + 1)
= 5x² + x - 4 = (5x - 1)(x + 1)
= 5x² + x - 4 = 5x² + 4x - 1
= 5x² + x - 4 - 5x² = 4x - 1
= x - 4 = 4x - 1
= x - 4 - 4x = - 1
= - 3x - 4 = - 1
= - 3x = - 1 + 4
= - 3x = 3
= x = 3/-3
= x = - 1
So, the answer is A. -1